Mathematical modeling supports the presence of neutrophil depriming in vivo. Issue 3 (3rd March 2014) - Summers, Charlotte; Chilvers, Edwin R.; Peters, A Michael
Abstract Following migration into the intestinal mucosa in inflammatory bowel disease (IBD), neutrophils enter the intestinal lumen and are excreted. This provides a basis for quantification of disease activity by measuring excreted label following injection of In‐111‐labeled neutrophils. In severe pan‐colitis, 50% of the injected In‐111 is typically recovered in the feces, indicating that 50% of neutrophil turnover is via fecal excretion. Neutrophils have an intravascular lifespan of ~10 h and a distribution volume of ~10 L, so total body neutrophil turnover is 10.N/10 cells/h, where N is the peripheral blood neutrophil count (cells/L). Neutrophil loss via the colon in a patient with 50% fecal In‐111 loss is therefore N/120 cells/min. Pan‐colonic mucosal‐blood flow in pan‐colitis is 200 mL/min, which would deliver N/5 neutrophils to the colon per min. Therefore, 5/120, or 4%, of incoming neutrophils undergo migration into inflamed bowel. If the 96% of nonmigrating cells exit in a primed state, then at steady state >90% of circulating neutrophils would be primed if no depriming took place. As the highest level of priming seen in IBD is ~40%, this indicates that depriming within the circulation must take place. Using the above values in the steady state equation relating priming rate to depriming rate plus primed‐cell destruction rate gives a mean depriming time of 35 min. We conclude that a very small proportion of neutrophils entering a site of inflammation migrate and that in vivo depriming must take place to limit the numbers of primed neutrophils in the circulation.